Jezikovna (ne)dostopnost pravic iz sistema socialnega varstva - Mišič, Luka (Slovenščina 2.0, 2025)
Social assistance is intended to prevent and alleviate poverty and social exclusion. It functions as a subsidiary safety net in relation to the rights provided under the system of social insurance. Social assistance rights - which include monetary assistance, as well as social services - are frequently claimed by vulnerable population groups. Members of these groups, such as the elderly, the long-term unemployed, or low-skilled workers, are often more exposed to the risks of poverty and social exclusion due to personal circumstances or other factors. Despite their vital societal role, social assistance rights are not necessarily effectively accessible or communicated through the legal provisions themselves. The legal norms governing them are characterized by the use of domain-specific legal language, which, more than in some other areas of law, departs significantly from everyday spoken language and thus hinders functional understanding. Consequently, particular importance must be placed on interpretive legal resources, such as handbooks and official government web-sites. However, state authorities do not always adjust the legal or statutory language in materials intended to inform individuals of their rights and obligations – such as the standard application form for claiming rights from public funds or the application for extraordinary financial social assistance - to the needs of legally untrained recipients or users. This can further limit access to legal protection.
Keywords: financial social assistance; jezikovna dostopnost; legal awareness; legal language; legally untrained party; linguistic accessibility; prava neuka stranka; pravni jezik; social assistance; social security; socialna pomoč; socialna varnost; socialno varstvo; spoznavanje prava; statutory language; zakonski jezik